Childhood Maltreatment and Depression in Adulthood in Chinese Female College Students: The Mediating Effect of Coping Style - Zheng, Zheng; Han, Wenyue; Zhou, Yuan; Zhang, Ning (Frontiers in Psychiatry, 2020)
Depression is the most common psychological disorder of female, with high disability rate and remarkable mortality rate. There is a lack of knowledge about childhood experience, coping style and adult depression. The aim of the present research was to enrich this knowledge by investigating the mediating effect of coping style between childhood maltreatment and depression in adulthood in Chinese female college students. Self-report questionnaires assessing childhood maltreatment, depression and coping style were completed in 738 participants. The results illustrated that childhood maltreatment was positively related to depression in adulthood while coping style was negatively related to depression. In addition, childhood maltreatment could influence adult depression through the mediating role of coping style. These findings indicate that childhood maltreatment and negative coping style are associated with depression in adulthood. Psychological intervention strategies for coping style could provide effective treatment direction for depression caused by childhood maltreatment.